1997
DOI: 10.1093/bja/79.3.306
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of volume controlled with pressure controlled ventilation during one-lung anaesthesia

Abstract: Pressure controlled ventilation (PCV) is an alternative mode of ventilation which is used widely in severe respiratory failure. In this study, PCV was used for one-lung anaesthesia and its effects on airway pressures, arterial oxygenation and haemodynamic state were compared with volume controlled ventilation (VCV). We studied 48 patients undergoing thoracotomy. After two-lung ventilation with VCV, patients were allocated randomly to one of two groups. In the first group (n = 24), one-lung ventilation was star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
0
8

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(114 citation statements)
references
References 25 publications
5
101
0
8
Order By: Relevance
“…Em estudo comparativo entre a PCV e a VCV, em pacientes com síndrome da angústia respiratória aguda (SARA) grave, foi observada uma menor redução no débito cardíaco no grupo da PCV, relatada como o resultado de uma melhora da pós-carga do ventrículo direito, devido a um melhor recrutamento alveolar, a uma redução da resistência vascular pulmonar e a diminuição da pressão intratorácica que facilitou uma melhor pré-carga de ambos os ventrículos 17 . Em outro estudo comparativo em pacientes submetidos à ventilação monopulmonar, foi observado que a Paw peek, a Paw plat e o shunt pulmonar foram significativamente maiores durante a VCV enquanto a PaCO 2 foi maior durante a PCV e concluíram que a PCV é uma alternativa à VCV, em pacientes que necessitem de ventilação monopulmonar, e pode ser superior à VCV em pacientes com doenças respiratórias 18 . No pós-operatório de pacientes de cirurgia cardíaca, os dois controles mostraram efeitos comparáveis em pacientes com função cardíaca preservada ou deprimida, mas nos pacientes com a PCV ocorreram maiores valores de índice cardía-co, diminuição da SVR e menores valores das pressões inspiratórias, quando comparados aos pacientes da VCV 19 .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Em estudo comparativo entre a PCV e a VCV, em pacientes com síndrome da angústia respiratória aguda (SARA) grave, foi observada uma menor redução no débito cardíaco no grupo da PCV, relatada como o resultado de uma melhora da pós-carga do ventrículo direito, devido a um melhor recrutamento alveolar, a uma redução da resistência vascular pulmonar e a diminuição da pressão intratorácica que facilitou uma melhor pré-carga de ambos os ventrículos 17 . Em outro estudo comparativo em pacientes submetidos à ventilação monopulmonar, foi observado que a Paw peek, a Paw plat e o shunt pulmonar foram significativamente maiores durante a VCV enquanto a PaCO 2 foi maior durante a PCV e concluíram que a PCV é uma alternativa à VCV, em pacientes que necessitem de ventilação monopulmonar, e pode ser superior à VCV em pacientes com doenças respiratórias 18 . No pós-operatório de pacientes de cirurgia cardíaca, os dois controles mostraram efeitos comparáveis em pacientes com função cardíaca preservada ou deprimida, mas nos pacientes com a PCV ocorreram maiores valores de índice cardía-co, diminuição da SVR e menores valores das pressões inspiratórias, quando comparados aos pacientes da VCV 19 .…”
Section: Resultsunclassified
“…A different comparative study with patients submitted to single-lung ventilation has observed significantly higher Paw peak, Paw plat and pulmonary shunt during VCV, while PaCO 2 was higher during PCV. The study has concluded that PCV is an alternative to VCV in patients needing single-lung ventilation, and may be better than VCV in respiratory disease patients 18 . In the postoperative period of cardiac surgeries, both controls had comparable effects in patients with preserved or depressed cardiac function, but PCV patients showed higher cardiac index values, decreased SVR and lower inspiratory pressure values, as compared to VCV patients 19 .…”
Section: Discussionmentioning
confidence: 96%
“…42 Whether PCV actually improves oxygenation is highly controversial, as studies have failed to find a consistent benefit. 43,44 Recommendation…”
Section: Pressure-control Vs Volume-control Ventilationmentioning
confidence: 99%
“…42 La controverse existe quant à savoir si la VPC améliore véritablement l'oxygénation; en effet, les études n'ont pas démontré de bienfait constant. 43,44 Recommandation…”
Section: Recrutementunclassified
“…Although controversial, pressure-controlled ventilation (PCV) is associated with improved lung mechanics and oxygenation relative to volume-controlled ventilation (VCV) in patients who require OLV because of its high initial flow rate and decelerating inspiratory flow pattern [8][9][10][11][12]. However, this high initial flow may cause shearing and traction forces on the alveoli, and the efficacy of PCV during OLV in the prone position has not been validated [13].…”
Section: Introductionmentioning
confidence: 99%